1999
DOI: 10.1177/0146167299025001010
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Social Identity: A New Framework and Evidence for the Impact of Different Dimensions

Abstract: The authors introduce a framework for organizing conceptualizations of social identity along four dimensions: perception of the intergroup context, in-group attraction, interdependency beliefs, and depersonalization. The authors suggest that the extent to which each dimension is evoked or assessed will have an impact on the consequences attributed to social identity. Two studies test hypotheses derived from the framework and investigate the psychometric properties of several scales. In Study 1, participants co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
221
0
11

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(245 citation statements)
references
References 43 publications
13
221
0
11
Order By: Relevance
“…The respondents' strength of identity with Canada and with their cultural group was measured using 6-item scales adapted from a scale developed by Brown et al (1986) which has been used extensively by intergroup relations researchers and which has good reliability and validity (Jackson & Smith, 1999). These 6-item scales were used in two previous studies of immigrants to measure their cultural and national identity and were shown to be both reliable and valid (Grant, 2007(Grant, , 2008.…”
Section: Identificationsmentioning
confidence: 99%
“…The respondents' strength of identity with Canada and with their cultural group was measured using 6-item scales adapted from a scale developed by Brown et al (1986) which has been used extensively by intergroup relations researchers and which has good reliability and validity (Jackson & Smith, 1999). These 6-item scales were used in two previous studies of immigrants to measure their cultural and national identity and were shown to be both reliable and valid (Grant, 2007(Grant, , 2008.…”
Section: Identificationsmentioning
confidence: 99%
“…People are more likely to perceive these attributes in ingroups than in outgroups (see Dion, 2000, or Jackson & Smith, 1999, for reviews), and social projection may be a mediating factor. There is, however, a difference: Ingroup-favoritism tends to be stronger in real groups than in laboratory groups (Mullen, Brown, & Smith, 1992) homogeneous than ingroups.…”
Section: Cognitive Consequencesmentioning
confidence: 99%
“…There is a great deal of variation and inconsistency in the way that group identifi cation is conceptualized and measured (see Ashmore et al, 2004;Cameron, 2004;Jackson & Smith, 1999). For example, a distinction among various dimensions or elements of identifi cation is made, such as evaluation, importance and attachment.…”
Section: Religious Identifi Cationmentioning
confidence: 99%